Assessment and formation mechanisms of scale deposits in tunnels of the ÖBB‐Infrastruktur AG – A subproject of the Task Force Drainage. Issue 3 (10th June 2020) - Eichinger, Stefanie; Leis, Albrecht; Boch, Ronny; Seywald, Christian; Dietzel, Martin
Abstract: Sinterbildungen in Drainagen von Eisenbahntunneln stellen für die Funktionalität und Instandhaltung des Entwässerungssystems eine große Herausforderung dar. Die Entfernung dieser Sinter verursacht neben hohen Kosten auch Einschränkungen der Anlagenverfügbarkeit. Wirkungsvolle Maßnahmen zur Reduzierung dieser Sinterbildungen reichen von gezielten bautechnischen Vorgaben für Baustoffe bis zum Einsatz von maßgeschneiderten Verhinderungs‐ und Reinigungsstrategien. Dies erfordert fundierte Kenntnisse über die Entstehungsmechanismen und die Typisierung der Sinter. Ziel dieser Studie ist die systematische Erfassung, Charakterisierung, Einteilung und Bewertung der Sinter in Hinblick auf deren Entstehungsmechanismen und den Einfluss von variablen Umgebungsfaktoren. Die Sinter aus 16 untersuchten Tunnelbauwerken bestehen vorwiegend aus Neubildungen der Minerale Kalzit, Aragonit, Brucit sowie Eisen(hydr)oxiden und detritischen Bestandteilen. Vier Sintertypen treten auf: (i) unverfestigt‐partikuläre, (ii) scherbenartige, (iii) poröse und (iv) kompakte Sinter. Die Sintertypen (ii) bis (iv) zeigen deutliche Hinweise auf mikrobielle Aktivitäten, welche die Ausbildung der einzelnen Sinter durch verschiedene metabolische Prozesse beeinflussen können. Die bestimmenden Faktoren für die Bildung der Sinter sind – neben der geogenen Zusammensetzung der im Drainagesystem befindlichen wässrigen Lösungen (Grundwasser/Oberflächenwasser) – die Wechselwirkung dieser Wässer mit den Bindemittelphasen der verwendeten Baustoffe und mit der Tunnelatmosphäre. Geogene Randbedingungen und technisch‐operative Vorgaben eines Tunnelbauwerks bestimmen die Art und Ausprägung des Sinters und können bei Kenntnis der fallspezifischen Reaktionsmechanismen durch individuelle Adaptierungen der Umgebungsbedingungen gezielt beeinflusst werden. Abstract: Scale deposit formation in drainage systems of railway tunnels represents a major challenge for their functionality and maintenance. The removal of these scale deposits causes high costs and restrictions of system availability. Effective measures to reduce scale deposit formation range from specification of the composition and structure of building materials to the application of tailored prevention and cleaning strategies. This requires advanced knowledge of the origin and type of scale deposits. The aim of this study is a systematic compilation, characterization, classification, and evaluation of scale deposits in relation to their formation mechanisms and the influence of variable environmental factors. The scale deposits from the 16 investigated tunnels mainly consist of the minerals calcite, aragonite, brucite as well as iron (hydr)oxides and detrital components. Four major types of scale deposits are distinguished: (i) unconsolidated‐particulate, (ii) shard‐like, (iii) porous, and (iv) compact scales. Types (ii) to (iv) show clear indications of microbial activity affecting the formation and appearance of individual deposits by various metabolic processes. The determining factors for the formation of scales – in addition to the geogenic composition of the aqueous solutions in the drainage system (groundwater / surface water) – are the variable interaction of these waters with the binding agents of the building materials used and the tunnel atmosphere. Geogenic conditions and technical‐operational specifications of a tunnel determine the type and character of scale deposits, which can be actively influenced based on the case‐specific reaction mechanisms by individual adaptations of environmental conditions.